A practical pilot experience of a Mindfulness program in university teacher—researcher training (2019)
This paper is aimed at relating a practical pilot experience of mindfulness meditation in a university context. This pilot experience aims to acquire an incipient understanding of the potential of this practice as a training mechanism for teaching staff. A qualitative method was used to record the mindfulness meditation practice experiences of teachers and instructors being trained; the trainees comprise the teaching staff that coordinates a learning environment called Context and region: Introduction to systemic thinking at Ibague University. A qualitative record and analysis process of the narratives of the practice experience were conducted based on the voices of the participants. Categories demonstrating aspects perceived as favorable or annoying with regard to the practice of mindfulness emerged. Benefits are perceived by participants in the following order: awareness, well-being, gratitude, and attention toward the other and oneself in the relationship. The annoyances are referred to as perceptions of physical discomfort present at the time of practicing mindfulness. The experience allowed a practical pilot that was shared with the team supporting the incorporation of attitudes related to the teaching role, personal experience, and the composition of teaching staff.